Performance of Broiler Chickens on Commercial Diets Mixed with Whole or Ground Wheat of Different Varieties - Yasar, Sulhattin (International Journal of Poultry Science, 2002)
To study the effects of mixing commercial diets with whole wheat on bird performance with respect to growing ages, each of four whole or ground wheat varieties was mixed with commercial diets at the presence or absence of enzyme at the following rates: 10% from 7 to 14 d of age, 20% from 14 to 21 d of age, 30% from 21 to 28 d of age, and 50% from 28 to 35 d of age. A control group of broiler chickens was fed only with commercial diets throughout. Birds performed well with the diets mixed with 10 and 20% wheat whether ground or whole. Feed intake of birds significantly (P<0.05) depressed only by the diets mixed with 50% of both whole and ground wheat. Weight gain and feed conversion ratio significantly (P<0.05) reduced with the diets mixed with 30 and 50% whole and ground wheat. There were no significant effects of wheat variety, wheat form and enzyme addition on the bird performance. Enzyme did not improve the performance of birds fed with the diets containing whole or ground wheat although there was a significant reduction in the digesta viscosity. Gut length was significantly longer in the birds fed on all the diets mixed with ground or whole wheat than the birds of control diets. It is concluded that birds can control feed intake unless they are not fed with the 50% wheat mixed diet until 28 d of age and grow optimally unless they are not fed with the 30% wheat mixed diet from 21 to 28 d of age. Furthermore, it is suggested that the fortification with some essential nutrients is necessary at early growing ages when mixing the diets with whole/ground wheat at high rates of <30%.